Has the financial crisis spurred demand for stronger state regulation? - Roth, Felix (Brussels, 2010)
"This paper analyses whether the financial crisis has affected citizens’ confidence in the free market economy and whether it has triggered citizens’ demand for a free market economy with stronger state regulations. Using panel data, the paper confirms that citizens’ confidence levels in the free market economy have decreased in most of the largest economies and demand for a free market economy with stronger state regulation has increased on both sides of the Atlantic. After analysing the determinants for citizens’ confidence in the free market economy and demand for a free market economy with stronger state regulation before and after the financial crisis, the author concludes that citizens’ net confidence loss in the free market economy seems to have been driven by rising unemployment rates, and citizens’ demand for stronger state regulation seems to have been driven by the real economic downturn in GDP growth."